2021
DOI: 10.1093/eurheartj/ehab724.1449
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between non-alcoholic fatty liver disease and acute coronary syndrome severity: is non-alcoholic fatty liver disease a risk marker of coronary atherosclerotic disease?

Abstract: Background/Introduction Non-alcoholic fatty liver disease (NAFLD) has been significantly associated with atherosclerotic disease independent of classical risk factors. However, the role of NAFLD in this context remains unclear. The systemic inflammation described in NAFLD related to liver disease progression may be one factor that can influence the progression and instability of atherosclerotic disease and, consequently, in the clinical characteristics of acute coronary syndrome (ACS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
2
0
4
Order By: Relevance
“…The frequent, significant, and sometimes independent association between NAFLD and CVD, especially atherosclerotic disease, has been demonstrated in different ways and has reinforced the hypothesis that this liver disease is at least one risk marker for CVD [25]. Among the possible links between CVD and NAFLD is the systemic inflammatory response related mainly to NASH [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequent, significant, and sometimes independent association between NAFLD and CVD, especially atherosclerotic disease, has been demonstrated in different ways and has reinforced the hypothesis that this liver disease is at least one risk marker for CVD [25]. Among the possible links between CVD and NAFLD is the systemic inflammatory response related mainly to NASH [6].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the correlation between the severity of NAFLD and the severity of CAD, in a cross-sectional study, severe NAFLD was related to the presence of coronary plaques, especially those at high risk, regardless of traditional risk factors [24]. Furthermore, a retrospective study showed a significant relationship between NAFLD and the severity of acute coronary syndrome (ACS), with the results also suggesting a correlation between the severity of both [25]. In a prospective cohort study, NAFLD was related to an increased risk of developing obstructive atherosclerotic lesions >50% and of percutaneous coronary interventions [26].…”
Section: Introductionmentioning
confidence: 98%
“…Метаболически-ассоциированная жировая болезнь печени (МАЖБП, старое название -неалкогольная жировая болезнь печени), развивающаяся в рамках метаболической дисфункции организма, рассматривается как фактор риска острого коронарного синдрома (ОКС) и может оказывать влияние на течение инфаркта миокарда (ИМ) [1]. В ряде исследований доказано, что у пациентов с МАЖБП наблюдается более тяжелое поражение коронарных артерий [2][3][4]. Тем не менее, связь между стеатозом печени и стеатогепатитом, т.е.…”
Section: особенности инфаркта миокарда с подъемом сегмента St при неа...unclassified
“…В связи с выполнением чрескожных вмешательств несколькими операторами рассчитывали значения κ Коэна для всех ангиографических показателей. Для оценки влияния набора факторов на вероятность наступления неблагоприятных событий в течение 18 5 (11,4) 3 (6,8) 6 (13,6) 15,5 (10;18,5) 0,453 0,568 0,816 0,950 0,847 0,128 0,048 <0,001 0,117 0,178 0,897 0,003 0,008 0,061 <0,001 <0,001 <0,001 <0,001 0,260 0,835 0,345 0,815 0,879 0,875 0,879 0,547 0,317 0,956 0,822 0,880 0,270 0,356 0,547 0,712 0,402 0,402 0,014 0,115 0,066 0,327 0,003 0,011 0,712 0,221 0,722 0,933 0,944 0,890 0,150 Примечание: ФВ ЛЖ -фракция выброса левого желудочка, ФПфибрилляция предсердий, ИМТ -индекс массы тела, ЧКВчрескожное вмешательство на коронарных артериях сосудов (извитость, кальциноз, признаки коллатерального кровотока) существенные различия между двумя группа не выявили. Итоговые значения шкалы SYN-TAX также не достоверно не отличались.…”
Section: материалы и методыunclassified
See 1 more Smart Citation